(untitled) (Indian Journal of Animal Production and Management, 2013)
An investigation was undertaken to study the udder, teat and body measurements as affected by parity and their relationship with milk yield and milking traits in 100 Gir cows at Cattle Breeding Farm, JAU, Junagadh. Mean udder length, width and depth were found to be (cm) 45.99 ± 2.07, 20.51 ± 0.99 and 20.29 ± 1.04, respectively and were significantly (P < 0.01) affected according to different orders of lactations. Positive and significant correlations were observed among all the udder measurements. However, the correlation was significant among Udder length, Udder width and daily milk yield (kg) (P<0.05). The average teat length (cm) and diameter (cm) in the present study were 7.07 ± 0.42 and 3.49 ± 0.21 cm respectively. A positive correlation existed between the average daily milk yield and the various teat measurements such as teat length, teat diameter, but the correlation was significant (P<0.05) only between the average teat diameter (cm) and the average daily milk yield (kg). Teat lengths and diameter were significantly (P<0.01) increasing with parity with respect to different shapes of teat. Overall body length, height at withers and heart girth were 126.24 ± 1.37 cm, 130.60 ± 1.65 cm and 165.13 ± 1.67 cm respectively. Body length (P< 0.05) and heart girth (P < 0.01) were significant with respect to different shapes of udder.